VD_FINDINFO Jug / 2024 / 385 vom 12. Oktober 2022 - VD Tribunal cantonal (2022)
PERSONNE PRIVÉE, CORRUPTION, CHANTAGE, FAUX INTELLECTUEL DANS LES TITRES, TENTATIVEDROIT PÉNAL | 156 CP, 22 al. 1 CP, 251 CP, 322novies CP, 433 CPP (CH)